Legal and policy framework for ecosystem-based adaptation to climate change in Malaysia: a reform oriented study - Ansari, Abdul Haseeb (2014)
Rise of average global temperature and its global disastrous impacts, due to unusual weather conditions, are escalating despite greenhouse gases (GHGs) reduction commitments under the Kyoto Protocol, as the mitigation mechanisms alone cannot do away with the sufferance of the people on long-term basis. It has to be combined with adaptation (Klein, Huq, Denton, & Downing, 2007). Adaptation to tenacious adverse impacts of climate change is crucial for alleviating the menace of the people. Adaptation within the context of UNFCCC is very restrictive and lacks detailed strategy. It is for this reason that mitigation measures combined with adaptation can best be practiced at regional, national and local level. (Koh and Lovleen, 2011; Sahraie, 2011, Othman, 2011). It has been said so in the Fourth Assessment Report of the IPCC, 2007. This is because although there are a number of strategies developed under its auspices, their implementation depends on a viable national adaptation plans and effective programmes of action within the Cancun Adaptation Framework and Nairobi Work Programme supported with encouraging transfer of environmentally sound technologies (ESTs), research support, financial support and support in capacity building. A successful programme at these levels depends on political will on the part of the state supported by all stakeholders, national and international, including people at the grass root level. All these have been well spelled out and discussed in the IPCC WGII AR5 entitled Climate Change 2014: Impacts, Adaptation and Vulnerability, released on 1 April 2014. (See infra)